2014
DOI: 10.1152/ajpregu.00539.2013
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of vascular function in premenopausal and recent postmenopausal women of similar age: effect of exercise training

Abstract: Menopause is associated with an accelerated decline in vascular function; however, whether this is an effect of age and/or menopause and how exercise training may affect this decline remains unclear. We examined a range of molecular measures related to vascular function in matched premenopausal and postmenopausal women before and after 12 wk of exercise training. Thirteen premenopausal and 10 recently postmenopausal [1.6 ± 0.3 (means ± SE) years after final menstrual period] women only separated by 3 yr (48 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 43 publications
0
61
0
Order By: Relevance
“…This study investigated the research questions by using samples from two separate studies with the aim of investigating the effects of floorball and spinning, respectively, on participants' cardiovascular and musculoskeletal health; the details as well as the results of studies are reported elsewhere (Mandrup, et al, 2017;Nyberg, et al, 2014). The studies were approved by the Ethics Committee of Copenhagen and Frederiksberg communities Region H (H-1-2012-150) and conducted in accordance with the guidelines of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigated the research questions by using samples from two separate studies with the aim of investigating the effects of floorball and spinning, respectively, on participants' cardiovascular and musculoskeletal health; the details as well as the results of studies are reported elsewhere (Mandrup, et al, 2017;Nyberg, et al, 2014). The studies were approved by the Ethics Committee of Copenhagen and Frederiksberg communities Region H (H-1-2012-150) and conducted in accordance with the guidelines of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Both the floorball and the spinning interventions were supervised and lasted 12 weeks. This intervention length and training frequency is sufficient to produce health benefits for the participants (Nyberg, et al, 2014). The floorball training sessions entailed 30 min of technical training exercises, including warm-up, followed by 30 min of floorball play 3 against 3 on a 12m x 20m court, in 4-6 min intervals separated by 1-3 min of recovery.…”
Section: Intervention Proceduresmentioning
confidence: 99%
“…Exercise training in middle-aged subjects improved forearm resistance vessel endothelial function (65) and NO bioavailability (281). Exercise training also improves endothelial function and/or increases the contribution of NO to basal tone in subjects with cardiovascular risk including hypertension (131), T2DM (193,223), obesity (202) and hypercholesterolemia (183,316) and in subjects with coronary artery disease (114, 315) and heart failure (115,116,192,194 plasma levels were found in postmenopausal women (227) and hypertensive subjects (123).…”
Section: Resistance Arteriesmentioning
confidence: 99%
“…However, the studies in which beneficial vascular effects of exercise training were not observed in late postmenopausal women were characterized by low to moderate exercise intensities, 15,28 whereas high-intensity aerobic training such as that introduced in the current study has been shown to be associated with improvements in vascular function. 29 As this latter training modality has superior cardiovascular effects compared with moderate intensity exercise in patients with heart failure, 30 it may be that exercise intensity is an essential factor for reversing vascular dysfunction in postmenopausal women. Hence, future studies should aim at determining the role of exercise intensity for the vascular adaptations with exercise training in both early and late postmenopausal women.…”
Section: Hypertensionmentioning
confidence: 99%
“…The present effect on vascular responsiveness to epoprostenol and acetylcholine is also in agreement with findings in a previous study on a similar group of pre-and postmenopausal women in whom biomarkers of vascular function were improved to a similar extent in the 2 groups after 12 weeks of exercise training. 29 Because estrogen is also an important regulator of vascular function, 23 it may be that exercise and estrogen share common signaling pathways. Accordingly, exercise leads to increases in vascular shear stress, which has been shown to activate phosphatidylinositol 3-kinase, which in turn activates protein kinase B (Akt) leading to activation of eNOS.…”
Section: Hypertensionmentioning
confidence: 99%